Adsorption Free Energy of Biphenyl and Aniline on the Surface of Graphene at Different Temperatures (Pragya Darshan प्रज्ञा दर्शन, 2025)
Adsorption free energy is important for the fundamental and practical aspect to describe  the nature of the reaction  and  to understand the  interconnection of the various ingredients involved in the adsorption process. It is also useful to understand the thermodynamics of the molecules in drug delivery, removal of contaminant and protein folding among other. Here, we used  TIP3P water model as a solvent to find out the adsorption free energy of the biphenyl and aniline  on the surface of graphene at different temperatures through NAMD (Nanoscale Molecular Dynamics) for simulations and VMD (Visual Molecular Dynamics) for molecular visualization and modeling of  the system. Overall calculations is performed within the framework of  Adaptive Biasing Force (ABF) method in different temperatures  at  1.03×105 Pascal pressure. The  value of  adsorption free energy of the systems  in the NPT ensembles  increase as increasing the temperature on both the systems. The calculation reveals that at the surface of graphene, biphenyl has a higher adsorption free energy than aniline. The  present calculation for biphenyl is in excellent agreement with the prior result at 300 K.